2007
DOI: 10.3168/jds.2007-0426
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Dry Glycerin to Early Postpartum Holstein Dairy Cows on Lactational Performance and Metabolic Profiles

Abstract: Effects of feeding a dry glycerin product (minimal 65% of food grade glycerol, dry powder) to 39 multiparous Holstein dairy cows (19 control and 20 glycerin-supplemented; lactation number = 2.2 +/- 1.3 SD) on feed intake, milk yield and composition, and blood metabolic profiles were investigated. Dry glycerin was fed at 250 g/d as a top dressing (corresponding to 162.5 g of glycerol/d) to the common lactating total mixed ration from parturition to 21 d postpartum. Individual milk was sampled from 2 consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
99
7
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(141 citation statements)
references
References 21 publications
18
99
7
17
Order By: Relevance
“…The lack of effects of adding glycerol to the total dry matter intake (TDMI) is consistent with other findings of research conducted in feedlot (DeFrain et al, 2004;Chung et al, 2007;Donkin et al, 2009;Wang et al, 2009). However, our findings were in contrast with the studies of Fisher et al (1971), who reported that glycerol stimulated consumption when the animals were fed 472 g/day in the concentrate, and Ogborn (2006), who stated that this trialcool has a depressive effect on consumption.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…The lack of effects of adding glycerol to the total dry matter intake (TDMI) is consistent with other findings of research conducted in feedlot (DeFrain et al, 2004;Chung et al, 2007;Donkin et al, 2009;Wang et al, 2009). However, our findings were in contrast with the studies of Fisher et al (1971), who reported that glycerol stimulated consumption when the animals were fed 472 g/day in the concentrate, and Ogborn (2006), who stated that this trialcool has a depressive effect on consumption.…”
Section: Resultssupporting
confidence: 78%
“…found that milk composition was not affected by the addition of glycerol at 150 g/kg of diet DM. Therefore, the lower milk fat content in the diet with the addition of glycerol is consistent with DeFrain et al (2004) and Chung et al (2007), who reported a lower production of milk fat when animals were fed glycerol.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations